EDUKASI PENGENALAN BUAH BUAHAN DALAM BAHASA INGGRIS MELALUI AUGMENTED REALITY BERBASIS ANDROID - Bun, Ayna Yodia; Pangaribuan, Hotma (LPPM Universitas Putera Batam, 2021)
The existence of English as a universal language or the main language of instruction throughout the world makes this language an important language in the world of Indonesian education. English continues to provide benefits in a wide scope, one of which is in the world of education. The advantage of English itself is that it has a meaning like the written form in Indonesian. The weakness that is recognized by general students is that the development of technology makes learning activities using printed books less motivating students to get to know their culture and knowledge. Through this research, the researcher wants to design interactive learning methods using technologies such as Android-based Augmented reality. Android is an operating system that is commonly found on smartphones to support daily activities. The Multimedia Development Life Cycle (MDLC) is a system design method used by researchers in the process of designing this learning application. The conclusion obtained in this study is that English learning applications using Android-based Augmented Reality technology can be an interesting and new additional learning medium as a support in recognizing basic English learning.